The Brand Image Bridge: Connecting Product Quality, Price Perception, and Social Media to Consumer Purchase Decisions - Muslimah, Leni; Tuti, Meylani; Effendi, (Technium Social Sciences Journal, 2025)
The purpose of this study is to analyze the influence of Product Quality, Price Perception, and Social Media Marketing on Purchasing Decisions through Brand Image. The population in this study was the Pawon Teh Leni Consumers. With the Accidental Sampling technique, namely, consumers who met directly with researchers and obtained 200 respondents. The study was conducted at Pawon The Leni Catering in December 2024, and the data analysis method used SEM with the help of Smart PLS 3 software. The results of the study show that Social media marketing influences purchasing decisions both directly and indirectly. This is different from the results of product quality and price perception, which do not directly influence purchasing decisions, but indirectly influence them through Brand Image. Meanwhile, Brand Image influences purchasing decisions. The results of this study contribute to Catering owners that social media marketing used by entrepreneurs can influence the company's Brand Image and consumer decisions in making purchases.